Analyzing Food Price Trends in the Context of Engel’s Law and the Prebisch-Singer Hypothesis - Baffes, John; Etienne, Xiaoli L. (World Bank, Washington, DC, 2015)
Income growth in emerging economies has often been cited as a key driver of the past decade’s com-modity price boom—the longest and broadest boom since World War II. This paper shows that income has a negative and highly significant effect on real food commodity prices, a finding that is consistent with Engel’s Law and Kindleberger’s thesis, the predecessors of the Prebisch-Singer hypothe-sis. The paper also shows that, in the long run, income influences real food prices mainly through the manufacturing price channel (the deflator), hence weakening the view that income growth exerts strong upward pressure on food prices. Other (short-term) drivers of food prices include energy costs, inventories, and monetary conditions.